1996
DOI: 10.1111/j.1432-1033.1996.0600h.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation and Enzyme Characteristics of a DNA‐Restrained Phosphatase in Chromatin‐Associated Complexes

Abstract: DNA-bound polypeptide complexes composed of several non-histone polypeptides that resisted harsh DNA deproteinization procedures were characterized. The three major polypeptides of these complexes have molecular masses of 62, 52, and 40 kDa. They constitute supramolecular structures that reside on isolated DNA in dense clusters. The supramolecular complexes were released from DNA as globular 12.8 ? 0.8-nm particles ; these particles were gradually disassembled to form smaller supramolecular structures. The DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Later the additional minor TBPs of 62, 52 and 40 kDa were described and it was reported that these proteins assemble in globules 12.8 nm in diameter (Loeffler et al, 1996). Similar globular structures were described for TBPs localized in interaction sites with the nuclear matrix, besides DNA and proteins (7 or 8 polypeptides) the globules contained RNA molecules (Chernokhvostov and Georgiev, 1990;Chernokhvostov et al, 1986Chernokhvostov et al, , 1989.…”
Section: Polypeptide Composition Of Tbps Its Tissue and Species Specmentioning
confidence: 75%
See 1 more Smart Citation
“…Later the additional minor TBPs of 62, 52 and 40 kDa were described and it was reported that these proteins assemble in globules 12.8 nm in diameter (Loeffler et al, 1996). Similar globular structures were described for TBPs localized in interaction sites with the nuclear matrix, besides DNA and proteins (7 or 8 polypeptides) the globules contained RNA molecules (Chernokhvostov and Georgiev, 1990;Chernokhvostov et al, 1986Chernokhvostov et al, , 1989.…”
Section: Polypeptide Composition Of Tbps Its Tissue and Species Specmentioning
confidence: 75%
“…Active enzyme was formed by subunits of 56 and 59 kDa (Loeffler et al, 1996;Juodka et al, 1995b). Later protein kinase activity was also found in the TBPs fraction of these cells.…”
Section: Enzyme Activities Of Tbpsmentioning
confidence: 90%
“…The electrophoretic mobilities, the glycoprotein nature [1, 7], the overlapping 12mer microsequence (Fig. 2) and the immunochemical data (Figs.…”
Section: Discussionmentioning
confidence: 98%
“…Complexes of this type were found to be attached to DNA isolated from human placenta and from murine tumor cells [6]. The DNA‐protein complexes survive treatments designed to dissociate DNA‐protein complexes, including cell lysis in the presence of SDS and proteinase K, salting out steps, prolonged incubation in 1% SDS or 4 M urea at 56°C and ethanol precipitations [6, 7]. Further characterization of the 52‐kDa nuclear glycoprotein by partial sequencing and by application of immunochemical and recombinant DNA techniques indicates that it is identical with the α‐1 protease inhibitor which points to a nuclear function of this protein.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation